Inflation as a Moderator of Interest Rate Fluctuations and Bank Profitability in Nigeria - GBADEBO, Adedeji Daniel (Journal of Financial and Behavioural Accounting, 2025)
This study investigates the novel moderating role of inflation in the relationship between interest rates and the profitability of listed deposit money banks in Nigeria over the period 2012–2022. Using panel data from 11 banks, the study applies Fixed Effects (FE) and Random Effects (RE) panel regression models, with profitability measured by Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM). Findings indicate that inflation significantly moderates the relationship between interest rates and both ROA and ROE, suggesting that asset- and equity-based measures of profitability are highly sensitive to inflationary dynamics. Conversely, the moderating effect on NIM is insignificant, implying that margins are relatively insulated from inflationary shocks. Theoretical implications highlight the asymmetrical impact of inflation on banking performance, reinforcing the relevance of the Fisher Effect, Modigliani-Miller intermediation theory, and Agency Cost theory in explaining bank behavior under inflationary conditions. Policy implications suggest that the Central Bank of Nigeria integrate inflation-sensitive indicators into supervisory frameworks, while banks strengthen risk management practices to mitigate macroeconomic vulnerabilities and sustain profitability. This study contributes uniquely by empirically demonstrating how inflation moderates interest rate transmission to bank profitability in a developing economy context.